Aramid composite nonwoven fabric, and preparation method and application thereof
Patent Information
- Application Number
- CN202511982016.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-25
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-12-25
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to an aramid composite nonwoven fabric, its preparation method and application, belonging to the field of reverse osmosis membrane support technology. Background Technology
[0002] Reverse osmosis technology is currently the most advanced and widely used core technology for advanced water treatment and seawater desalination. Its core component, the reverse osmosis membrane, typically employs a composite membrane structure, consisting of an ultra-thin and dense polyamide active separation layer supported on a porous substrate. The performance of this porous support substrate directly determines the separation performance, mechanical strength, and long-term operational reliability of the final reverse osmosis membrane.
[0003] Currently, commercially available reverse osmosis membranes generally use polyester nonwoven fabric as the porous support substrate. However, as reverse osmosis technology develops to meet higher requirements, the traditional single polyester nonwoven fabric substrate is gradually revealing its inherent technical limitations: First, there is an irreconcilable contradiction between surface smoothness and pore structure in polyester nonwoven fabrics. Achieving a smooth surface through high temperature and pressure inevitably leads to the collapse of the pore structure, a decrease in porosity, and a denser material. Conversely, maintaining ideal high porosity requires sufficient pressure, resulting in a loose fiber network, increased surface fuzz, and deterioration of smoothness. This contradiction makes it difficult for traditional substrates to simultaneously meet the dual requirements of high-performance reverse osmosis membranes for both surface quality and permeability.
[0004] Secondly, the substrate lacks sufficient mechanical strength and dimensional stability. In high-pressure applications, traditional polyester nonwoven fabrics, due to their limited fiber modulus, are prone to creep and compression densification under long-term operation, resulting in thinner substrates, narrower water flow channels, and increased system pressure drop, causing irreversible reduction in water production flux.
[0005] Furthermore, traditional reinforcement methods have significant drawbacks. Increasing the basis weight of the substrate or using coarser fibers to improve strength often further sacrifices porosity and surface smoothness. On the other hand, simple mixing or post-lamination composite methods that introduce other high-performance fibers often face problems such as weak interfacial bonding and complex processes.
[0006] Therefore, there is an urgent need in this field to develop a new type of reverse osmosis membrane support substrate that can fundamentally solve the inherent contradiction between surface flatness and pore structure, while taking into account excellent mechanical strength and dimensional stability, so as to provide a reliable foundation for the preparation of next-generation high-performance reverse osmosis membranes. Summary of the Invention
[0007] This invention addresses the shortcomings of existing technologies by providing an aramid composite nonwoven fabric, its preparation method, and its application. The aramid composite nonwoven fabric, through a sandwich structure design, solves the contradiction between surface smoothness and high porosity when traditional polyester nonwoven fabric is used as a reverse osmosis membrane support substrate. This invention performs differentiated optimization for the different functional requirements of the coated and uncoated surfaces, significantly improving the mechanical strength and dimensional stability of the substrate to resist creep and compression under high pressure.
[0008] The technical solution of this invention to solve the above-mentioned technical problems is as follows: a method for preparing aramid composite nonwoven fabric, wherein the preparation method is as follows: S1. Preparation of base fabric and base paper: Preparation of aramid paper base paper 1: Aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 1; the oven-dry basis weight of the aramid paper base paper 1 is 15-20 g / m³. 2 ; Preparation of polyester nonwoven fabric: Polyester main fibers and polyester bonding fibers are loosened and stirred, and then formed by inclined wire wet forming to obtain polyester nonwoven fabric with a basis weight of 30-40 g / m². Preparation of aramid paper base paper 2: Aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 2; the oven-dry basis weight of the aramid paper base paper 2 is 10-15 g / m³. 2 ; S2, Composite: The aramid paper base paper 1, the polyester nonwoven fabric base cloth, and the aramid paper base paper 2 are sequentially stacked, pressed, and dried to obtain a stacked blank. S3, Five-stage continuous process: The composite blank is subjected to preheating and pressing, hot pressing, longitudinal stretching, transverse stretching and cooling and shaping in sequence to obtain aramid composite nonwoven fabric.
[0009] Furthermore, in step S1, when preparing the polyester nonwoven fabric, the polyester main fiber is 60-85 parts by weight fraction, the polyester bonding fiber is 15-40 parts, and the sum of the weight fractions of the polyester main fiber and the polyester bonding fiber is 100 parts. The polyester main fiber has a fineness of 0.5-0.8D, a length of 5-6mm, and a melting point temperature of 258-262℃. The polyester bonding fiber has a fineness of 1.2-2D and a length of 3-6mm. The polyester bonding fiber is a core-sheath structure polyester fiber with a sheath melting point of 100-130℃ and a core melting point of 258-262℃.
[0010] Furthermore, in step S1, when preparing aramid paper base paper 1, the weight fraction of aramid short-cut fibers is 15-25 parts, meta-aramid precipitated fibers is 35-45 parts, and para-aramid nanofibers is 35-45 parts; and the sum of the weight fractions of aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers is 100 parts. The beating degree of the meta-aramid precipitated fiber is 60-80°SR.
[0011] Furthermore, in step S1, when preparing the aramid paper base paper 2, the weight fraction of aramid short-cut fibers is 28-37 parts, meta-aramid precipitated fibers is 32-40 parts, and para-aramid nanofibers is 28-40 parts; and the sum of the weight fractions of aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers is 100 parts. The beating degree of the meta-aramid precipitated fiber is 60-80°SR.
[0012] Furthermore, the five-stage continuous process in step S3 is completed continuously on an integrated production line consisting of five functional units, with each functional unit arranged horizontally along the material travel direction; wherein: The first unit consists of two vertically arranged rollers, forming the first roller gap; The second unit consists of two vertically arranged rollers, forming a second roller gap; The third unit consists of two vertically arranged rollers, forming a third roller gap; The fourth unit is a transverse tensioning device; The fifth unit contains two vertically arranged rollers, forming the fourth roller gap; The stacked blanks pass horizontally through the first group of units, the second group of units, the third group of units, the fourth group of units, and the fifth group of units in sequence.
[0013] Furthermore, during the preheating pressing process, the temperature is 180℃-200℃, the linear pressure is 150N / mm-300N / mm, and the linear velocity is 5.0-15.0 m / min; During the hot pressing process, the temperature is 230℃-250℃, the linear pressure is 150N / mm-250N / mm, and the linear velocity of the hot pressing process is the same as that of the preheating pressing process.
[0014] Furthermore, during the longitudinal stretching process, the inlet linear velocity is controlled at 5.0-15.0 m / min, the outlet linear velocity is controlled at 5.3-17.3 m / min, and the ratio of the linear velocity of the outlet roller to the linear velocity of the inlet roller is 1.05-1.15. During the longitudinal stretching process, the temperature is 200℃-220℃ and the linear pressure is 40N / mm-80N / mm.
[0015] Furthermore, the temperature of the transverse stretching is 180℃-210℃, the linear velocity of the transverse stretching is the same as the exit velocity of the longitudinal stretching, and during the transverse stretching process, the ratio of the exit width to the inlet width of the tenter frame is controlled to be 1.10-1.25. During the cooling and shaping process, the temperature is controlled below 80°C, and the linear velocity of the cooling and shaping process is the same as that of the transverse stretching process.
[0016] The present invention also discloses an aramid composite nonwoven fabric, which is prepared by the preparation method described in the present invention.
[0017] The present invention also discloses an application of aramid composite nonwoven fabric, which is used in the field of reverse osmosis membranes. The side of the aramid composite nonwoven fabric with the aramid paper base 1 is the coated side; the side of the aramid composite nonwoven fabric with the aramid paper base 2 is the uncoated side.
[0018] The beneficial effects of this invention are: (1) Achieved a synergistic improvement in surface smoothness, high porosity, and excellent mechanical strength: By introducing para-aramid nanofibers into a highly freed meta-aramid precipitated fiber network, a multi-level fiber structure of "micron-submicron-nano" was formed. The highly freed precipitated fibers, like cement, fill large pores to form a fine base, while the para-aramid nanofibers undergo nanoscale modification to further fill microscopic defects. The inherent high modulus and high strength of aramid fibers or para-aramid nanofibers provide a robust skeleton for the composite material to resist high pressure, fundamentally inhibiting creep and compression densification of the reverse osmosis membrane substrate.
[0019] This invention first prepares a smooth-surfaced composite nonwoven fabric through preheating and hot pressing, and then uses a hot-pressing-stretching synergistic molding and cooling-setting method to prepare a high-porosity, high-strength composite nonwoven fabric. This solves the problem that traditional polyester nonwoven fabrics for reverse osmosis membranes require either high smoothness or low porosity. The smooth surface of the high-strength composite nonwoven fabric of this invention can significantly improve the desalination rate and enhance the anti-fouling ability of the reverse osmosis membrane, while its high porosity ensures an increase in the permeate flux of the reverse osmosis membrane.
[0020] In summary, by perfectly combining "micro-nano synergistic smoothing" at the material level with "sequential synergistic control" at the process level, the "impossible triangle" between surface smoothness, high porosity, and mechanical strength of traditional reverse osmosis membrane support substrates has been successfully broken, achieving a synergistic leap in the performance of the three.
[0021] (2) Significantly improved the mechanical strength and dimensional stability of polyester nonwoven fabrics for reverse osmosis membranes: First, the sandwich structure of aramid paper-polyester-aramid paper utilizes the excellent modulus and rigidity of aramid fibers to construct a robust supporting skeleton, effectively resisting the compression densification and creep of the substrate in high-pressure reverse osmosis applications, avoiding irreversible flux attenuation caused by substrate flattening, and greatly extending the service life of the membrane.
[0022] Secondly, by introducing a specific proportion (35-45 parts) of para-aramid nanofibers into the aramid paper base paper 1, and synergizing with meta-aramid precipitated fibers with high freeness (60-80°SR), a multi-layered, high-strength fiber network from micrometers to nanometers is formed inside the aramid paper, which significantly improves the strength of the aramid paper base paper itself, thus contributing extremely high mechanical strength to the final composite product.
[0023] Finally, through the synergistic effect of hot pressing and stretching in the five-stage process, gradient fusion and interface strengthening between layers were achieved. Under pressure, the polyester melt penetrates into the micro-nano pores of the aramid paper to form a three-dimensional interlocking structure. The stretching process causes the fibers to intertwine and form "fiber bridges," which are then permanently fixed under cooling and shaping. This ensures a strong interlayer bond, eliminates the risk of delamination, and achieves efficient stress transfer between layers.
[0024] (3) The fiber interface bonding was optimized, breaking through the limitations of traditional reinforcement methods: Traditional methods of introducing high-performance fibers through simple mixing or lamination often result in weak interfacial bonding. This invention, through the synergistic effect of multiple fiber components, constructs a multi-level, highly effective interfacial bonding network ranging from macroscopic to microscopic levels and from physical to chemical structures. Primary bonding (physical anchoring and mechanical interlocking): The polyester bonding fibers of the core-sheath structure melt and flow during hot pressing, penetrating into the fiber network of the aramid paper. After cooling, a strong three-dimensional mechanical interlocking structure is formed, achieving firm anchoring on a macroscopic scale.
[0025] Secondary bonding (hydrogen bond bridging of nanofibers): The strong hydrogen bonding effect of para-aramid nanofibers plays a crucial role. These nanofibers not only enhance the bonding within the aramid paper, but also, through their huge specific surface area at the interface between the aramid and polyester layers, form dense hydrogen bond sites with the ester groups on the surface of the polyester fibers. These hydrogen bonds act like countless invisible "molecular bridges" or "claws," tightly "weaving" the aramid and polyester, which originally had very different chemical properties, together at the molecular scale.
[0026] Tertiary bonding (enhanced by high-freezing precipitated fibers): High-freezing meta-aramid precipitated fibers provide a huge specific surface area and more bonding sites, further strengthening the bonding within the aramid paper and providing a denser and more stable substrate for hydrogen bonding bridging of nanofibers.
[0027] Synergistic Effect: These three mechanisms are not simply superimposed, but rather work synergistically. Physical interlocking forms the "skeleton" of the bond, while hydrogen bonding acts as a strong "adhesive" between the layers, creating a stable interface structure with "mechanical interlocking as the body and hydrogen bonding as the ribs." This allows the three-layer composite structure to achieve high strength reinforcement while fundamentally eliminating the risk of interface delamination, realizing efficient stress transfer between layers, and overcoming the technical limitations of traditional methods that cannot simultaneously guarantee high strength reinforcement and strong interlayer bonding.
[0028] (4) High integration of production processes and good consistency of product performance: The five-stage continuous process used in the preparation method is completed on an integrated production line. The uniformity and stability of product performance are ensured by precise speed and tension control of each unit (rollers that can be driven independently by servo motors or vector control frequency conversion motors). Detailed Implementation
[0029] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described in detail below. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0031] A method for preparing an aramid composite nonwoven fabric, wherein the preparation method comprises: S1. Preparation of base fabric and base paper: Preparation of aramid paper base paper 1: Aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 1; the oven-dry basis weight of the aramid paper base paper 1 is 15-20 g / m³. 2 ; Preparation of polyester nonwoven fabric: Polyester main fibers and polyester bonding fibers are loosened and stirred, and then formed by inclined wire wet forming to obtain polyester nonwoven fabric with a basis weight of 30-40 g / m². Preparation of aramid paper base paper 2: Aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 2; the oven-dry basis weight of the aramid paper base paper 2 is 10-15 g / m³. 2 ; S2, Composite: The aramid paper base paper 1, the polyester nonwoven fabric base cloth, and the aramid paper base paper 2 are sequentially stacked, pressed, and dried to obtain a stacked blank. S3, Five-stage continuous process: The composite blank is subjected to preheating and pressing, hot pressing, longitudinal stretching, transverse stretching and cooling and shaping in sequence to obtain aramid composite nonwoven fabric.
[0032] Furthermore, in step S1, when preparing the polyester nonwoven fabric, the polyester main fiber is 60-85 parts by weight fraction, the polyester bonding fiber is 15-40 parts, and the sum of the weight fractions of the polyester main fiber and the polyester bonding fiber is 100 parts. The polyester main fiber has a fineness of 0.5-0.8D, a length of 5-6mm, and a melting point temperature of 258-262℃. The polyester bonding fiber has a fineness of 1.2-2D and a length of 3-6mm. The polyester bonding fiber is a core-sheath structure polyester fiber with a sheath melting point of 100-130℃ and a core melting point of 258-262℃.
[0033] Furthermore, in step S1, when preparing aramid paper base paper 1, the weight fraction of aramid short-cut fibers is 15-25 parts, meta-aramid precipitated fibers is 35-45 parts, and para-aramid nanofibers is 35-45 parts; and the sum of the weight fractions of aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers is 100 parts. The beating degree of the meta-aramid precipitated fiber is 60-80°SR.
[0034] Furthermore, in step S1, when preparing the aramid paper base paper 2, the weight fraction of aramid short-cut fibers is 28-37 parts, meta-aramid precipitated fibers is 32-40 parts, and para-aramid nanofibers is 28-40 parts; and the sum of the weight fractions of aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers is 100 parts. The beating degree of the meta-aramid precipitated fiber is 60-80°SR.
[0035] More specifically, the aramid chopped fibers are para-aramid chopped fibers or meta-aramid chopped fibers.
[0036] Specifically, in step S2, aramid paper base paper 1 is located on the upper layer, corresponding to the coating layer of the reverse osmosis membrane substrate; aramid paper base paper 2 is located on the lower layer, corresponding to the uncoated layer of the reverse osmosis membrane substrate.
[0037] Furthermore, the five-stage continuous process in step S3 is completed continuously on an integrated production line consisting of five functional units, with each functional unit arranged horizontally along the material travel direction; wherein: The first unit consists of two vertically arranged rollers, forming the first roller gap; The second unit consists of two vertically arranged rollers, forming a second roller gap; The third unit consists of two vertically arranged rollers, forming a third roller gap; The fourth unit is a transverse tensioning device; The fifth unit contains two vertically arranged rollers, forming the fourth roller gap; The stacked blanks pass horizontally through the first group of units, the second group of units, the third group of units, the fourth group of units, and the fifth group of units in sequence.
[0038] More specifically, the five-stage continuous process in step S3 is as follows: (1) Preheating and pressing: The composite blank is passed through the first roller gap of the first group of units and preliminarily composited under the conditions of temperature of 180℃~200℃ and linear pressure of 150N / mm~300N / mm; the linear speed of the first group of units is controlled at 5.0-15.0 m / min; (2) Hot pressing: The pre-hot-pressed billet is introduced into the second roller gap of the second unit and further hot-pressed composite is carried out under the conditions of temperature of 230℃~250℃ and linear pressure of 150N / mm~250N / mm; the linear speed of the second unit is the same as that of the first unit. (3) Longitudinal stretching: The hot-pressed billet is introduced into the third roll gap of the third unit; the inlet linear velocity of the third unit is controlled at 5.0-15.0 m / min, and the outlet linear velocity is controlled at 5.3-17.3 m / min; the billet is subjected to longitudinal stretching by controlling the ratio of the linear velocity of the outlet roll (V2) to the linear velocity of the inlet roll (V1) in the third unit; the linear velocity ratio V2 / V1 is controlled at 1.05-1.15; the temperature of the third roll gap is maintained at 200℃-220℃, and the linear pressure is 40N / mm-80N / mm; (4) Lateral stretching: The longitudinally stretched billet is introduced into the lateral stretching device of the fourth unit; the device clamps the two sides of the billet with clamps and stretches the billet laterally under the condition of 180℃-210℃; the linear velocity of the fourth unit is the same as the exit velocity of the third unit; the lateral stretching is achieved by controlling the ratio of the exit width (W2) of the tenter frame to the inlet width (W1), and the width ratio W2 / W1 is controlled between 1.10 and 1.25; (5) Cooling and shaping: The biaxially stretched billet is introduced into the fourth roller gap of the fifth unit. This group of rollers is a cooling roller, and the surface temperature is controlled below 80°C. The linear speed of the fifth unit is the same as that of the fourth unit; the microporous structure is shaped while maintaining tension.
[0039] An aramid composite nonwoven fabric is prepared using the method described in this invention. This aramid composite nonwoven fabric has a three-layer asymmetric structure (a high-basis-weight aramid paper base 1 / polyester nonwoven fabric / a low-basis-weight aramid paper base 2). Its upper layer (coated surface) has extremely high smoothness and density, while the lower layer (uncoated surface) ensures strength while also possessing good water permeability and operability. Overall, it combines high surface smoothness, high porosity, and high mechanical strength.
[0040] An application of aramid composite nonwoven fabric, which is used in the field of reverse osmosis membranes, particularly as a supporting substrate for high-performance reverse osmosis membranes.
[0041] Example 1 The preparation method of an aramid composite nonwoven fabric is as follows: S1. Preparation of base fabric and base paper: (1) Preparation of aramid paper base paper 1: Para-aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 1; the oven-dry basis weight of the aramid paper base paper 1 is 18 g / m³. 2 ; By weight fraction, the amount of para-aramid chopped fiber is 20 parts, the amount of meta-aramid precipitated fiber is 40 parts, and the amount of para-aramid nanofiber is 40 parts; the beating degree of the meta-aramid precipitated fiber is 70°SR.
[0042] (2) Preparation of polyester nonwoven fabric: The polyester main fiber and polyester bonding fiber are loosened and stirred, and then formed by inclined wire wet forming to obtain a polyester nonwoven fabric with a basis weight of 35g / m². The amount of polyester main fiber added is 75 parts by weight, and the amount of polyester bonding fiber added is 25 parts. The polyester main fiber has a fineness of 0.6D, a length of 5mm, and a melting point temperature of 260℃. The polyester bonding fiber has a fineness of 1.5D and a length of 3mm; the polyester bonding fiber is a core-sheath structure polyester fiber with a sheath melting point of 110℃ and a core melting point of 260℃.
[0043] (3) Preparation of aramid paper base paper 2: Para-aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 2; the oven-dry basis weight of the aramid paper base paper 2 is 12 g / m³. 2 ; By weight fraction, the amount of para-aramid chopped fiber is 35 parts, the amount of meta-aramid precipitated fiber is 35 parts, and the amount of para-aramid nanofiber is 30 parts; the freeness of the meta-aramid precipitated fiber is 65°SR.
[0044] S2, Composite: The aramid paper base paper 1, the polyester nonwoven fabric base cloth, and the aramid paper base paper 2 are sequentially stacked, pressed, and dried to obtain a stacked blank. S3, Five-stage continuous process: The laminated preform is subjected to preheating and pressing, hot pressing, longitudinal stretching, transverse stretching, and cooling and shaping in sequence to obtain aramid composite nonwoven fabric, under the following specific conditions: (1) Preheating and pressing: The composite blanks are passed through the first roller gap and preliminarily compounded under the conditions of temperature of 190℃, linear pressure of 200N / mm, and linear speed of 10m / min; (2) Hot pressing: The pre-hot-pressed composite blank is introduced into the second roller gap and further hot-pressed composite is carried out at a temperature of 240℃ and a linear pressure of 200N / mm, with a linear speed of 10m / min. (3) Longitudinal stretching: The hot-pressed composite billet is introduced into the third roll gap; the billet is subjected to longitudinal stretching by controlling the ratio of the linear velocity of the exit roll to the inlet roll (stretching ratio V2 / V1 = 1.08), while the temperature of the third roll gap is maintained at 210℃ and the linear pressure is 60N / mm. (4) Lateral stretching: The longitudinally stretched stacked billet is introduced into the lateral stretching device; under the condition of 200℃, the billet is stretched in the lateral direction by controlling the ratio of the exit width to the inlet width of the tenter frame (stretching ratio W2 / W1 = 1.18); (5) Cooling and shaping: The biaxially stretched composite blank is introduced into the fourth roller gap. This set of rollers is a cooling roller, and the surface temperature is controlled at 60°C. The microporous structure is shaped while maintaining tension to obtain aramid composite nonwoven fabric.
[0045] Example 2 The preparation method of an aramid composite nonwoven fabric is as follows: S1. Preparation of base fabric and base paper: (1) Preparation of aramid paper base paper 1: Meta-aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 1; the oven-dry basis weight of the aramid paper base paper 1 is 20 g / m³. 2 ; By weight fraction, the meta-aramid chopped fibers comprise 15 parts, the meta-aramid precipitated fibers comprise 45 parts, and the para-aramid nanofibers comprise 40 parts; the beating degree of the meta-aramid precipitated fibers is 60°SR.
[0046] (2) Preparation of polyester nonwoven fabric: The polyester main fiber and polyester bonding fiber are loosened and stirred, and then formed by inclined wire wet forming to obtain a polyester nonwoven fabric with a basis weight of 30g / m². The amount of polyester main fiber added is 60 parts by weight, and the amount of polyester bonding fiber added is 40 parts. The polyester main fiber has a fineness of 0.5D, a length of 6mm, and a melting point temperature of 260℃. The polyester bonding fiber has a fineness of 1.2D and a length of 5mm; the polyester bonding fiber is a core-sheath structure polyester fiber with a sheath melting point of 100℃ and a core melting point of 260℃.
[0047] (3) Preparation of aramid paper base paper 2: Meta-aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 2; the oven-dry basis weight of the aramid paper base paper 2 is 15 g / m³. 2 ; By weight fraction, the meta-aramid chopped fibers comprise 28 parts, the meta-aramid precipitated fibers comprise 32 parts, and the para-aramid nanofibers comprise 40 parts; the freeness of the meta-aramid precipitated fibers is 60°SR.
[0048] S2, Composite: The aramid paper base paper 1, the polyester nonwoven fabric base cloth, and the aramid paper base paper 2 are sequentially stacked, pressed, and dried to obtain a stacked blank. S3, Five-stage continuous process: The laminated preform is subjected to preheating and pressing, hot pressing, longitudinal stretching, transverse stretching, and cooling and shaping in sequence to obtain aramid composite nonwoven fabric, under the following specific conditions: (1) Preheating and pressing: The composite blanks are passed through the first roller gap and preliminarily compounded under the conditions of temperature of 180℃, linear pressure of 200N / mm, and linear speed of 5m / min. (2) Hot pressing: The pre-hot-pressed composite blank is introduced into the second roller gap and further hot-pressed composite is carried out at a temperature of 230℃ and a linear pressure of 200N / mm, with a linear speed of 5m / min. (3) Longitudinal stretching: The hot-pressed composite billet is introduced into the third roll gap; the billet is subjected to longitudinal stretching by controlling the ratio of the linear velocity of the exit roll to the inlet roll (stretching ratio V2 / V1 = 1.05), while the temperature of the third roll gap is maintained at 200℃ and the linear pressure is 80N / mm. (4) Lateral stretching: The longitudinally stretched composite billet is introduced into the lateral stretching device; under the condition of a temperature of 190℃, the billet is stretched in the lateral direction by controlling the ratio of the exit width to the inlet width of the tenter frame (stretching ratio W2 / W1 = 1.12); (5) Cooling and shaping: The biaxially stretched composite blank is introduced into the fourth roller gap. This set of rollers is a cooling roller, and the surface temperature is controlled at 50°C. The microporous structure is shaped while maintaining tension to obtain aramid composite nonwoven fabric.
[0049] Example 3 The preparation method of an aramid composite nonwoven fabric is as follows: S1. Preparation of base fabric and base paper: (1) Preparation of aramid paper base paper 1: Para-aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 1; the oven-dry basis weight of the aramid paper base paper 1 is 15 g / m³. 2 ; By weight fraction, the amount of para-aramid chopped fiber is 15 parts, the amount of meta-aramid precipitated fiber is 40 parts, and the amount of para-aramid nanofiber is 45 parts; the freeness of the meta-aramid precipitated fiber is 80°SR.
[0050] (2) Preparation of polyester nonwoven fabric: The polyester main fiber and polyester bonding fiber are loosened and stirred, and then formed by inclined wire wet forming to obtain a polyester nonwoven fabric with a basis weight of 40g / m². The amount of polyester main fiber added is 85 parts by weight, and the amount of polyester bonding fiber added is 15 parts. The polyester main fiber has a fineness of 0.8D, a length of 5mm, and a melting point temperature of 260℃. The polyester bonding fiber has a fineness of 2D and a length of 6mm; the polyester bonding fiber is a core-sheath structure polyester fiber with a sheath melting point of 130℃ and a core melting point of 260℃.
[0051] (3) Preparation of aramid paper base paper 2: Para-aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 2; the oven-dry basis weight of the aramid paper base paper 2 is 10 g / m³. 2 ; By weight fraction, the para-aramid chopped fibers comprise 37 parts, the meta-aramid precipitated fibers comprise 35 parts, and the para-aramid nanofibers comprise 28 parts; the freeness of the meta-aramid precipitated fibers is 80°SR.
[0052] S2, Composite: The aramid paper base paper 1, the polyester nonwoven fabric base cloth, and the aramid paper base paper 2 are sequentially stacked, pressed, and dried to obtain a stacked blank. S3, Five-stage continuous process: The laminated preform is subjected to preheating and pressing, hot pressing, longitudinal stretching, transverse stretching, and cooling and shaping in sequence to obtain aramid composite nonwoven fabric, under the following specific conditions: (1) Preheating and pressing: The composite blanks are passed through the first roller gap and preliminarily compounded under the conditions of 200℃ temperature, 200N / mm linear pressure, and 15m / min linear speed. (2) Hot pressing: The pre-hot-pressed composite blank is introduced into the second roller gap and further hot-pressed composite is carried out at a temperature of 250℃ and a linear pressure of 200N / mm, with a linear speed of 15m / min. (3) Longitudinal stretching: The hot-pressed composite billet is introduced into the third roll gap; the billet is subjected to longitudinal stretching by controlling the ratio of the linear velocity of the exit roll to the inlet roll (stretching ratio V2 / V1 = 1.15), while the temperature of the third roll gap is maintained at 220℃ and the linear pressure is 40N / mm. (4) Lateral stretching: The longitudinally stretched composite billet is introduced into the lateral stretching device; under the condition of a temperature of 210℃, the billet is stretched in the lateral direction by controlling the ratio of the exit width to the inlet width of the tenter frame (stretching ratio W2 / W1 = 1.22); (5) Cooling and shaping: The biaxially stretched composite blank is introduced into the fourth roller gap. This set of rollers is a cooling roller, and the surface temperature is controlled at 70°C. The microporous structure is shaped while maintaining tension to obtain aramid composite nonwoven fabric.
[0053] Comparative Example 1 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that: aramid paper base paper 2 was not used in Comparative Example 1; instead, aramid paper base paper 1 was directly prepared to an oven-dry basis weight of 30 g / m². Other process conditions were the same as in Example 1. Specifically, the conditions for preparing aramid paper base paper 1 were as follows: Preparation of aramid paper base paper 1: Para-aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 1; the oven-dry basis weight of the aramid paper base paper 1 is 30 g / m³. 2 ; By weight fraction, the amount of para-aramid chopped fiber is 20 parts, the amount of meta-aramid precipitated fiber is 40 parts, and the amount of para-aramid nanofiber is 40 parts; the beating degree of the meta-aramid precipitated fiber is 70°SR.
[0054] Comparative Example 2 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that: aramid paper base paper 1 was not used in Comparative Example 2; instead, aramid paper base paper 2 was directly prepared to have an oven-dry basis weight of 30 g / m². Other process conditions were the same as in Example 1. Specifically, the conditions for preparing aramid paper base paper 2 were as follows: Preparation of aramid paper base paper 2: Para-aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 2; the oven-dry basis weight of the aramid paper base paper 2 is 30 g / m³. 2 ; By weight fraction, the amount of para-aramid chopped fiber is 35 parts, the amount of meta-aramid precipitated fiber is 35 parts, and the amount of para-aramid nanofiber is 30 parts; the freeness of the meta-aramid precipitated fiber is 65°SR.
[0055] Comparative Example 3 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that: aramid paper base 1 was not used in Comparative Example 3, and the polyester nonwoven fabric base was made into a polyester nonwoven fabric with a basis weight of 65 g / m²; other process conditions were the same as in Example 1, wherein the specific conditions for preparing the polyester nonwoven fabric base were: Preparation of polyester nonwoven fabric: Polyester main fibers and polyester bonding fibers are loosened and stirred, and then formed by inclined wire wet process to obtain polyester nonwoven fabric with a basis weight of 65g / m². The amount of polyester main fiber added is 75 parts by weight, and the amount of polyester bonding fiber added is 25 parts. The polyester main fiber has a fineness of 0.6D, a length of 5mm, and a melting point temperature of 260℃. The polyester bonding fiber has a fineness of 1.5D and a length of 3mm; the polyester bonding fiber is a core-sheath structure polyester fiber with a sheath melting point of 110℃ and a core melting point of 260℃.
[0056] Comparative Example 4 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that: when preparing aramid paper base paper 1 in Comparative Example 4, the beating degree of the meta-aramid precipitated fibers used was 50°SR (lower than the beating degree specified in this invention).
[0057] Comparative Example 5 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that: when preparing aramid paper base paper 1 in Comparative Example 5, the beating degree of the meta-aramid precipitated fibers used was 85°SR (higher than the beating degree specified in this invention).
[0058] Comparative Example 6 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that the proportion of para-aramid nanofibers was reduced when preparing the aramid paper base paper 1 in Comparative Example 6, as detailed below: When preparing aramid paper base paper 1, the weight fractions are as follows: 20 parts of aramid short-cut fibers, 40 parts of meta-aramid precipitated fibers, and 30 parts of para-aramid nanofibers.
[0059] Comparative Example 7 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that the proportion of para-aramid nanofibers was increased when preparing the aramid paper base paper 1 in Comparative Example 7, as detailed below: When preparing aramid paper base paper 1, the weight fractions are as follows: 20 parts of aramid short-cut fibers, 40 parts of meta-aramid precipitated fibers, and 50 parts of para-aramid nanofibers.
[0060] Comparative Example 8 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that in this Comparative Example 8, V2 / V1 = 1 during the longitudinal stretching process, and other process conditions were the same as in Example 1.
[0061] Comparative Example 9 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that in Comparative Example 9, V2 / V1 = 1.25 during the longitudinal stretching process, and other process conditions were the same as in Example 1.
[0062] Comparative Example 10 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that the temperature during the longitudinal stretching process in Comparative Example 10 was 190°C (lower than the temperature conditions specified in this invention), and other process conditions were the same as in Example 1.
[0063] Comparative Example 11 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that the temperature during the longitudinal stretching process in Comparative Example 11 was 230°C (higher than the temperature conditions specified in this invention), and other process conditions were the same as in Example 1.
[0064] Comparative Example 12 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that the pressure during the longitudinal stretching process in Comparative Example 12 was 30 N / mm (lower than the pressure conditions specified in this invention), and other process conditions were the same as in Example 1.
[0065] Comparative Example 13 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that the pressure during the longitudinal stretching process in Comparative Example 13 was 90 N / mm (higher than the pressure conditions specified in this invention), and other process conditions were the same as in Example 1.
[0066] Comparative Example 14 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that W2 / W1 = 1.05 during the transverse stretching process in Comparative Example 14, and other process conditions were the same as in Example 1.
[0067] Comparative Example 15 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that in Comparative Example 15, W2 / W1 = 1.30 during the transverse stretching process, and other process conditions were the same as in Example 1.
[0068] Comparative Example 16 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that the temperature during the transverse stretching process in Comparative Example 16 was 170°C (lower than the temperature conditions specified in this invention), and other process conditions were the same as in Example 1.
[0069] Comparative Example 17 Aramid composite nonwoven fabric was prepared using the same method as in Example 1, except that the temperature during the transverse stretching process in Comparative Example 17 was 220°C (higher than the temperature conditions specified in this invention), and other process conditions were the same as in Example 1.
[0070] The polyester nonwoven fabrics prepared in the above examples and comparative examples were subjected to performance tests, and the test methods involved are as follows: I. Porosity Testing Methods: Step 1: Take a circular plate with a diameter of 4cm, dry the sample in a vacuum drying oven at 90℃ for 4 hours to remove moisture and volatile substances, and quickly take out the sample after cooling. Record the initial dry weight as m1.
[0071] Step 2: Place the sample from Step 1 into a vacuum-capable desiccator. Pour sufficient isopropanol into the desiccator, ensuring the liquid completely submerges the sample. Seal the container, connect the vacuum pump, and begin evacuation. Maintain a pressure above -0.095 MPa for 2-4 hours, or until no more bubbles are observed escaping from the sample. Slowly release the vacuum, allowing atmospheric pressure to further force the liquid into the pores.
[0072] Step 3: After impregnation, use tweezers to remove the sample from the isopropanol. Hold the sample vertically above the isopropanol surface briefly (about 2-3 seconds) to allow excess liquid to drip off. Immediately place the sample on a balance and weigh it in its saturated state, recording the weight as m2.
[0073] Step 4: Prepare a beaker, fill it with an appropriate amount of isopropanol, and place it on a balance. Suspend the sample (from Step 3) using a very fine metal wire or nylon thread, ensuring it is completely submerged in the isopropanol in the beaker and does not contact the beaker wall or bottom. After the balance reading stabilizes, record this weight (m³). (Note: This value is negative). Calculate the porosity using the following formula: P (%) = - [ (m2- m1) / m3] × 100%.
[0074] II. Other indicator testing methods: 1. Quantitative testing: Detected according to the method in GB / T 451.2; 2. Thickness: Refer to GB / T 451.3 standard; 3. Tightness = Basis weight / Thickness; 4. Tensile strength: Tested according to the method of GB / T 12914; 5. Interlayer bond strength: Tested according to the method of GB / T 26203; 6. Air permeability: Tested according to the method of GB / T 24218.15; 7. Surface smoothness: The reference standard is GB / T 456-2002; 8. Pressure resistance: The reference standard is GB / T 32373-2025; The various indicators of the polyester nonwoven fabrics in the above embodiments and comparative examples were tested, and the specific test results are shown in Tables 1 and 2 below.
[0075] Table 1 Performance Test Results Table 2. Other performance test results As can be seen from Tables 1 and 2, the aramid composite nonwoven fabrics prepared in Examples 1-3 have excellent tensile strength and interlayer bonding strength, high surface smoothness, certain air permeability and porosity, and good pressure resistance.
[0076] The comparison of the experimental results of Comparative Examples 1-3 and Example 1 shows that if the sandwich structure of aramid paper-polyester-aramid paper is not used, the tensile strength of the composite nonwoven fabric is significantly reduced, and the pressure resistance of the reverse osmosis membrane substrate is significantly reduced. The desalination rate and water flux change rate of Comparative Examples 1-3 are significantly improved.
[0077] The sandwich structure of aramid paper-polyester-aramid paper in the aramid composite nonwoven fabric of the present invention utilizes the excellent modulus and rigidity of aramid fibers to construct a robust supporting skeleton, effectively resisting the compression densification and creep of the substrate in high-pressure reverse osmosis applications, avoiding irreversible flux attenuation caused by the flattening of the substrate, and greatly extending the service life of the membrane.
[0078] The comparison of the experimental results of Comparative Examples 4-5 and Example 1 shows that the freeness of Comparative Example 4 is less than 60°SR, which makes it impossible to form an effective fiber bonding network. This results in a decrease in the tensile strength of the product and the smoothness of the coated surface, causing surface roughness during the subsequent coating preparation of the reverse osmosis membrane and significantly reducing the desalination rate of the reverse osmosis membrane. Moreover, the low freeness of the meta-aramid precipitated fibers will cause a decrease in the interlayer bonding strength on the paper and an increase in the desalination rate and water flux change rate.
[0079] In Comparative Example 5, the freeness was higher than 80°SR. Although the interlayer bonding was strong, the tensile strength was reduced, the pore structure was destroyed, and the air permeability and water flux were drastically reduced, thus lowering the product's usability. Therefore, controlling the freeness within the range of 60°SR to 80°SR is more conducive to achieving synergistic optimization of various key properties, resulting in an aramid composite nonwoven fabric with excellent overall performance.
[0080] The comparison of experimental results between Comparative Examples 6-7 and Example 1 shows that in Comparative Example 6, the tensile strength, coating surface smoothness, interlayer bonding strength, and initial desalination rate of the aramid composite nonwoven fabric are significantly reduced, while the pressure resistance (the rate of change in desalination rate and the rate of change in water flux) are significantly reduced. In Comparative Example 7, the tensile strength, air permeability, porosity, and initial water flux of the composite nonwoven fabric are significantly reduced.
[0081] In summary, there is a narrow optimal window for the content of para-aramid nanofibers. Deviating from this window (as in Comparative Examples 6 and 7) will lead to severe degradation of product performance, failing to meet the requirements of high-performance reverse osmosis membranes. Therefore, controlling its content within a reasonable range is more conducive to achieving a synergistic improvement in both high desalination rate and high flux.
[0082] The comparison of the experimental results of Comparative Examples 8-9 and Example 1 shows that the tensile strength, surface smoothness of the coating, interlayer bonding strength, initial water flux and desalination rate, and pressure resistance of Comparative Examples 8-9 are significantly reduced.
[0083] The data above shows that there is a critical threshold for the longitudinal stretch ratio. When the stretch ratio is below this threshold (e.g., <1.05), it not only fails to effectively improve the performance of the polyester nonwoven fabric, but also introduces localized defects such as large pores on the substrate surface, leading to an increase in the air permeability CV value, uneven pore structure, and consequently, damage to the integrity of the reverse osmosis membrane separation layer, resulting in an initial desalination rate lower than that of the unstretched substrate. The preferred stretch ratio range of this invention (1.05-1.15) is more conducive to obtaining aramid composite nonwoven fabrics with excellent performance.
[0084] A comparison of the experimental results of Comparative Examples 10, 11 and Example 1 shows that the tensile strength, surface smoothness of the coating, interlayer bonding strength, initial water flux, desalination rate, and pressure resistance of Comparative Examples 10-11 are significantly reduced. The increased air permeability CV value in Comparative Examples 10-11 indicates that its pore structure is uneven.
[0085] When the temperature is too low (as in Comparative Example 10), the material is brittle under tension, which can lead to fiber breakage and microcracks. The resulting product has a rough surface, weak interlayer bonding, and uneven pore structure, ultimately resulting in low desalination rate and water flux, deterioration of mechanical properties, and decreased pressure resistance.
[0086] When the temperature is too high (as in Comparative Example 11), the material exhibits viscous flow, which leads to molecular chain disorientation, pore collapse, and failure of bonded fibers. As a result, the strength of the product decreases, the pore structure becomes uneven, and ultimately, the water flux and desalination rate are low, the mechanical properties deteriorate, and the pressure resistance decreases.
[0087] A comparison of the experimental results of Comparative Examples 12 and 13 with Example 1 shows that the tensile strength, surface smoothness of the coating, interlayer bonding strength, initial water flux, desalination rate, and pressure resistance of Comparative Examples 12-13 are significantly reduced. The increased air permeability CV value in Comparative Examples 12-13 indicates that its pore structure is uneven.
[0088] When the linear pressure is too low (as in Comparative Example 12), effective interlayer bonding and surface leveling cannot be achieved, resulting in weak interlayer bonding strength and a rough surface. This manifests as low tensile strength due to interface damage, uneven pore structure, and deterioration of the initial desalination rate due to defects in the reverse osmosis membrane separation layer. Simultaneously, the loose structure is easily compressed under pressure, leading to low water flux and desalination rate with accelerated decay (large rate of change).
[0089] When the longitudinal tensile pressure is too low, it cannot effectively shape and fix the fiber network during the stretching process. This leads to two serious consequences: First, the fibers undergo non-cooperative slippage and tearing during stretching, instead of uniform orientation, directly creating defective pores with significant size variations; second, the bonded fiber melt cannot be uniformly distributed due to the lack of driving pressure, resulting in sparse and uneven interlayer bonding points, failing to form a stable overall skeleton to maintain the long-term stability of the pore structure. Therefore, excessively low linear pressure is one of the fundamental reasons for uneven pore structure, leading to initial performance degradation and insufficient long-term stability of the product.
[0090] When the linear pressure is too high (as in Comparative Example 13), it can cause irreversible crushing damage to the pore structure, resulting in a severe decrease in porosity and uneven pore structure. The most direct manifestation of this is a sharp loss of initial water flux, rendering the product useless. At the same time, excessive compaction can make the material brittle, and reduce its tensile strength and interlayer bonding strength.
[0091] Therefore, by using the optimal pressure range defined by this invention, a strong interlayer bond and excellent surface smoothness can be achieved without damaging the pore structure, thereby simultaneously obtaining a high initial desalination rate, high water flux and excellent long-term operational stability (good pressure resistance).
[0092] A comparison of the experimental results of Comparative Examples 14 and 15 with Example 1 shows that the surface smoothness, interlayer bonding strength, initial water flux, desalination rate, and pressure resistance of the coating surfaces in Comparative Examples 14-15 are significantly reduced. Simultaneously, the transverse tensile strength of Comparative Example 14 and the tensile strength of Comparative Example 15 are also significantly reduced. The increased air permeability (CV) value in Comparative Examples 14-15 indicates an uneven pore structure.
[0093] A comparison of the experimental results of Comparative Examples 16 and 17 with Example 1 shows that the tensile strength, surface smoothness of the coating, interlayer bonding strength, initial water flux, desalination rate, and pressure resistance of Comparative Examples 16-17 are significantly reduced. The increased air permeability CV value in Comparative Examples 16-17 indicates that their pore structure is uneven.
[0094] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0095] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing an aramid composite nonwoven fabric, characterized in that, The preparation method is as follows: S1. Preparation of base fabric and base paper: Preparation of aramid paper base paper 1: Aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 1; the oven-dry basis weight of the aramid paper base paper 1 is 15-20 g / m³. 2 ; Preparation of polyester nonwoven fabric: Polyester main fibers and polyester bonding fibers are loosened and stirred, and then formed by inclined wire wet forming to obtain polyester nonwoven fabric with a basis weight of 30-40 g / m². Preparation of aramid paper base paper 2: Aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers are loosened, stirred, and then formed by inclined wire wet forming to obtain aramid paper base paper 2; the oven-dry basis weight of the aramid paper base paper 2 is 10-15 g / m³. 2 ; S2, Composite: The aramid paper base paper 1, the polyester nonwoven fabric base cloth, and the aramid paper base paper 2 are sequentially stacked, pressed, and dried to obtain a stacked blank. S3, Five-stage continuous process: The laminated blank is subjected to preheating and pressing, hot pressing, longitudinal stretching, transverse stretching and cooling and shaping in sequence to obtain aramid composite nonwoven fabric; In step S1, when preparing aramid paper base paper 1, the weight fractions are as follows: 15-25 parts of aramid short-cut fibers, 35-45 parts of meta-aramid precipitated fibers, and 35-45 parts of para-aramid nanofibers; and the sum of the weight fractions of aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers is 100 parts. The beating degree of the meta-aramid precipitated fibers used in the preparation of aramid paper base paper 1 is 60-80°SR; During the longitudinal stretching process, the inlet linear velocity is controlled at 5.0-15.0 m / min, the outlet linear velocity is controlled at 5.3-17.3 m / min, and the ratio of the linear velocity of the outlet roller to the linear velocity of the inlet roller is 1.05-1.
15. During the longitudinal stretching process, the temperature is 200℃-220℃, and the linear pressure is 40N / mm-80N / mm; The temperature of the transverse stretching is 180℃-210℃, the linear velocity of the transverse stretching is the same as the exit velocity of the longitudinal stretching, and during the transverse stretching process, the ratio of the exit width to the inlet width of the tenter frame is controlled to be 1.10-1.
25.
2. The method for preparing an aramid composite nonwoven fabric according to claim 1, characterized in that, In step S1, when preparing the polyester nonwoven fabric, the polyester main fiber is 60-85 parts by weight, the polyester bonding fiber is 15-40 parts, and the sum of the weight parts of the polyester main fiber and the polyester bonding fiber is 100 parts. The polyester main fiber has a fineness of 0.5-0.8D, a length of 5-6mm, and a melting point temperature of 258-262℃. The polyester bonding fiber has a fineness of 1.2-2D and a length of 3-6mm. The polyester bonding fiber is a core-sheath structure polyester fiber with a sheath melting point of 100-130℃ and a core melting point of 258-262℃.
3. The method for preparing an aramid composite nonwoven fabric according to claim 1, characterized in that, In step S1, when preparing aramid paper base paper 2, the weight fraction of aramid short-cut fibers is 28-37 parts, meta-aramid precipitated fibers is 32-40 parts, and para-aramid nanofibers is 28-40 parts; and the sum of the weight fractions of aramid short-cut fibers, meta-aramid precipitated fibers, and para-aramid nanofibers is 100 parts. The beating degree of the meta-aramid precipitated fibers used in the preparation of aramid paper base paper 2 is 60-80°SR.
4. The method for preparing an aramid composite nonwoven fabric according to claim 1, characterized in that, Step S3, the five-stage continuous process, is completed continuously on an integrated production line consisting of five functional units, with each functional unit arranged horizontally along the material travel direction; wherein: The first unit consists of two vertically arranged rollers, forming the first roller gap; The second unit consists of two vertically arranged rollers, forming a second roller gap; The third unit consists of two vertically arranged rollers, forming a third roller gap; The fourth unit is a transverse tensioning device; The fifth unit contains two vertically arranged rollers, forming the fourth roller gap; The stacked blanks pass horizontally through the first group of units, the second group of units, the third group of units, the fourth group of units, and the fifth group of units in sequence.
5. The method for preparing an aramid composite nonwoven fabric according to claim 1, characterized in that, During the preheating and pressing process, the temperature is 180℃-200℃, the linear pressure is 150N / mm-300N / mm, and the linear velocity is 5.0-15.0 m / min. During the hot pressing process, the temperature is 230℃-250℃, the linear pressure is 150N / mm-250N / mm, and the linear velocity of the hot pressing process is the same as that of the preheating pressing process.
6. The method for preparing an aramid composite nonwoven fabric according to claim 1, characterized in that, During the cooling and shaping process, the temperature is controlled below 80°C, and the linear velocity of the cooling and shaping process is the same as that of the transverse stretching process.
7. An aramid composite nonwoven fabric, characterized in that, The aramid composite nonwoven fabric is prepared by the preparation method described in any one of claims 1-6.
8. An application of the aramid composite nonwoven fabric according to claim 7, characterized in that, The aramid composite nonwoven fabric is used in the field of reverse osmosis membranes. The side of the aramid composite nonwoven fabric with the aramid paper base paper 1 is the coated side; the side of the aramid composite nonwoven fabric with the aramid paper base paper 2 is the uncoated side.
Citation Information
Patent Citations
Meta-aramid paper and preparation method thereof
CN119593242A
Polyester non-woven fabric and preparation method and application thereof
CN120840226A
Two -sided compound aramid paper
CN206521650U